Handling death and bereavement at work - Charles-Edwards, David, 1938- (Routledge, 2005)
3,500 people die every day in the UK and their death may affect the workplace in many ways. If the deceased was an employee, for example, or the partner of an employee, their manager will need to sort out the difficult issues that arise from death. This workbook places bereavement on the management agenda rather than leaving managerial responses to chance. It is a guide for anyone in an organisation who, in the case of death, has to take responsibility, from managers, human resource and occupational health specialists, to welfare officers and trade union representatives.